2020
DOI: 10.3390/jcm9041141
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Children and Adolescents with Cerebral Palsy—A Systematic Literature Review

Abstract: Cardiac autonomic dysfunction has been reported in patients with cerebral palsy (CP). The aim of this study was to assess the existing literature on heart rate variability (HRV) in pediatric patients with CP and a special attention was paid to the compliance of the studies with the current HRV assessment and interpretation guidelines. A systematic review was performed in PubMed, Web of Science, and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases searched for English language publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 131 publications
(246 reference statements)
0
15
0
Order By: Relevance
“…Spectral powers at LF and HF bands are commonly attributed to sympathetic and vagal, and vagal influences alone on HR, respectively. Thus, coaches and sport practitioners should be aware that changes in the respiratory rate may confound spectral indices [ 53 ]. It has been suggested that depth of breathing could be even more important than its rate [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spectral powers at LF and HF bands are commonly attributed to sympathetic and vagal, and vagal influences alone on HR, respectively. Thus, coaches and sport practitioners should be aware that changes in the respiratory rate may confound spectral indices [ 53 ]. It has been suggested that depth of breathing could be even more important than its rate [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of tidal volumes using, e.g., mouthpieces may affect HRV data [ 17 , 85 ]. Moreover, there is no optimal solution on how to record and control respiratory depth and rate in HRV studies [ 44 , 53 ]. One possible solution for future studies in athletes could be to implement the Pneumonitor 2 or 3, a portable device that would register respiratory pattern (both depth and rate) together with single-lead ECG (enough to estimate aforementioned parameters), motion, and/or pulse oximetry (saturation, pulse wave) designed for environmental physiology analyses and sports medicine [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the HRV reveals how well the autonomic nervous system regulates cardiac rhythm and how responsive the heart is [ 19 ]. Compared to children with normal development, pediatric patients with CP were demonstrated to show considerably greater resting heart rates, lower heart rate variability (HRV), and different autonomic responses to movement stimuli [ 20 ].…”
Section: Introductionmentioning
confidence: 99%